The Representation of Fiqh Values in the Translation of Moral and Ethical Terminology in the Book Fiqh an-Nisā’ - Imama Nur Layliyah; Nurul Aini Octavia (UIN Mahmud Yunus Batusangkar, 2026)
The translation of fiqh books presents challenges in transferring normative terms that convey legal and ethical values into the target language. The main issue addressed in this study is how fiqh values are represented in the translation of moral and ethical criteria terms found in the Arabic text Fiqh an-Nisā’. This study aims to examine the translation patterns employed and how the translator balances the accuracy of legal meanings with readers’ comprehensibility. The research applies a qualitative descriptive method using two data sources: the Arabic text Fiqh an-Nisā’ and its Indonesian translation, Fiqih Wanita Empat Madzhab. The data consist of terms belonging to the category of moral and ethical criteria, which were collected through observation and note-taking techniques, and then analyzed based on the equivalence of form, meaning, and function. The findings reveal three patterns in representing fiqh values: partial negotiation, full resistance, and partial resistance. Full resistance preserves fiqh terms in their original form, partial negotiation adjusts form and meaning to make them more communicative, while partial resistance retains some normative values with certain shifts. These findings indicate that the translator seeks to balance terminological accuracy with ease of understanding in the translation of fiqh texts.